Clinical Features and Treatments of Upper Lumbar Disc Herniations - Kim, Duk-Sung (The Korean Neurosurgical Society, 2010)
OBJECTIVE: Disc herniations at the L1-L2 and L2-L3 levels are different from those at lower levels of the lumbar spine with regard to clinical characteristics and surgical outcome. Spinal canals are narrower than those of lower levels, which may compromise multiple spinal nerve roots or conus medullaris. The aim of this study was to evaluate the clinical features and surgical outcomes of upper lumbar disc herniations. METHODS: We retrospectively reviewed the clinical features of 41 patients who had undergone surgery for single disc herniations at the L1-L2 and L2-3 levels from 1998 to 2007. The affected levels were L1-L2 in 14 patients and L2-L3 in 27 patients. Presenting symptoms and signs, patient characteristics, radiologic findings, operative methods, and surgical outcomes were investigated. RESULTS: The mean age of patients with upper lumbar disc was 55.5 years (ranged 31 to 78). The mean follow-up period was 16.6 months. Most patients complained of back and buttock pain (38 patients, 92%), and radiating pain in areas such as the anterior or anterolateral aspect of the thigh (32 patients, 78%). Weakness of lower extremities was observed in 16 patients (39%) and sensory disturbance was presented in 19 patients (46%). Only 6 patients (14%) had undergone previous lumbar disc surgery. Discectomy was performed using three methods : unilateral laminectomy in 27 cases, bilateral laminectomy in 3 cases, and the transdural approach in 11 cases, which were performed through total laminectomy in 10 cases and unilateral laminectomy in 1 case. With regard to surgical outcomes, preoperative symptoms improved significantly in 33 patients (80.5%), partially in 7 patients (17%), and were aggravated in 1 patient (2.5%). CONCLUSION: Clinical features of disc herniations at the L1-L2 and L2-L3 levels were variable, and localized sensory change or pain was rarely demonstrated. In most cases, the discectomy was performed successfully by conventional posterior laminectomy. On the other hand, in large central broad based disc herniation, when the neural elements are severely compromised, the posterior transdural approach could be an alternative.